1998
DOI: 10.1111/j.1399-0039.1998.tb03102.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐DR and ‐DQ alleles in Italian patients with melanoma

Abstract: Controversial data have been reported about HLA alleles and susceptibility to melanoma. Our investigation was undertaken to analyze the relationship between HLA alleles distribution in patients with melanoma and susceptibility to the tumor, in order to study the possible correlation between HLA class II DQA1, DQB1 and DRB1 genes involved in immune recognition, and melanoma, usually considered a highly immunogenic tumor. We therefore typed by means of PCR‐SSP (sequence‐specific primers) 53 Italian patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Negative associations were found between DQB1*0302/0303 and CMM, whereas a positive association was found for DQB1*0501 in two Italian studies. 99,100 In Japanese patients with CMM, a positive association was found with DQB1*0302, whereas negative associations were reported for DRB1*0802 and DQA1*0101/ 0104/0401. 101 Finally, in a British population, an increase in the frequency of DQB1*0303 was found among CMM patients.…”
Section: Immune-related Genesmentioning
confidence: 77%
See 1 more Smart Citation
“…Negative associations were found between DQB1*0302/0303 and CMM, whereas a positive association was found for DQB1*0501 in two Italian studies. 99,100 In Japanese patients with CMM, a positive association was found with DQB1*0302, whereas negative associations were reported for DRB1*0802 and DQA1*0101/ 0104/0401. 101 Finally, in a British population, an increase in the frequency of DQB1*0303 was found among CMM patients.…”
Section: Immune-related Genesmentioning
confidence: 77%
“…One study reported no association between DQB1*0301 and risk of CMM, 98 whereas another found a slight, but not significant, positive association with susceptibility, 99 and yet another indicated a negative association with risk of CMM. 100 The variability of these results could, in part, be due to sample size, patient series heterogeneity, control populations, or technical differences in detecting HLA genotype. 94 Other studies have shown associations between CMM and additional HLA alleles.…”
Section: Immune-related Genesmentioning
confidence: 97%
“…In the English population, similar results were obtained for DQB1 ∗ 03:01 in terms of the risk of melanoma, but the most frequent allele in patients was HLA-DQB1 ∗ 03:03 as opposed to HLA-DQB1 ∗ 03:01 [ 16 ]. Conversely, Lulli et al observed a decrease in the frequency of HLA-DQB1 ∗ 03 and all haplotypes that included three alleles within the family DQB1 ∗ 03:01, DQB1 ∗ 03:02, and DQB1 ∗ 03:03, although this study included only 53 melanoma patients [ 17 ]. Luongo et al also observed no association between HLA class II genes and the susceptibility to melanoma [ 10 ].…”
Section: Introductionmentioning
confidence: 92%
“…30 Conversely, Lulli et al found a negative association. 31 Positive associations were also found with HLA-DQB1*0302 and negative associations with DRB1*0802, DQA1*0101/0104 and DQA1*0401 in Japanese populations with melanoma. 32 An increased frequency of HLA-DQB1*0303 was found in the British Caucasian population, and a decrease in the frequency of DQB1*0302 and DQB1*0303 was detected in two series of Italian patients, as well as an increase in DQB1*0501.…”
Section: Dr1 Was Associated With Multiple Basal Cell Carcinomas At Anmentioning
confidence: 92%